Distance Learning Materials For Islamic Religious Education Students In The Covid-19 Pandemic - Sutisna; M. Dahlan R (CV. Inara, 2021)
The COVID-19 pandemic has acted as a catalyst for change in a variety of areas of life, including education. Education, which was previously conducted solely in the classroom, has evolved into technology-based distance learning, posing challenges for students at all levels of the educational process, including students. This study aims to analyze Islamic Religious Education students' knowledge, problems, and efforts to improve course understanding. A semi-structured questionnaire and the probability snowball sampling approach were used to conduct an online survey. The responders were from the second semester of eight classes, and a total of 180 statements were accepted. Distance learning expertise During distant learning, 63.71 percent stated they comprehended the process, and 42 percent said they felt their parents' attention. Students cited slow learning, excessive costs, and not ideal as problems in this survey, with 51.2 percent, 63 percent, and 63.3 percent, respectively, expressing their dissatisfaction. 74.4 percent of students reported that they were making significant efforts to improve their comprehension of studying and listening courses, with 43 percent of students attempting to ask questions and 90.6 seeking for references in order to better their understanding of the course.